2007
DOI: 10.1590/s1413-86702007000600007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing risk behaviors and prevalence of sexually transmitted and blood-borne infections among female crack cocaine users in salvador - Bahia, Brazil

Abstract: Crack cocaine use is associated with risky sexual behaviors and sexually transmitted infections (STIs), including HIV. We investigated sociodemographic and behavioral characteristics and infection rates in female crack cocaine users from impoverished communities of Salvador, Bahia, Brazil. A sample of 125 female crack cocaine users was recruited. Overall, the interviewees had low educational level and high rate of unemployment (close to 90%). Onethird (37%) reported having traded sex for money or drugs, and 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
36
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 48 publications
8
36
2
2
Order By: Relevance
“…The result was below that found among crack users in Bahía, with 2.4% (14) and similar to that among adults in Criciúma, with 1.53% (21) .…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…The result was below that found among crack users in Bahía, with 2.4% (14) and similar to that among adults in Criciúma, with 1.53% (21) .…”
contrasting
confidence: 69%
“…A higher frequency was found by researchers in a separate study (14) , in which 49.3% of crack users reported that they rarely used them, in spite of their being available for free in the health services.…”
Section: Discussionmentioning
confidence: 70%
“…A study evaluated a sample of 125 women crack users from the underprivileged communities in Salvador, Bahia State, Brazil, of whom 90% had low education levels and high unemployment, 37% reported having sex for money or drugs and 58% reported they had not used condoms during sexual intercourse over the previous 30 days. The study reinforces the concept that women who use crack are a significant vulnerable group in regard to STIs transmission and unplanned pregnancies 28 .…”
Section: Introductionsupporting
confidence: 84%
“…Recent Canadian studies reported consistently high rates of HIV (∼10%-45%) and/or HCV infection (∼40%-85%) among crack users (DeBeck et al, 2009;Fischer et al, 2006Fischer et al, , 2010Leonard et al, 2008;Shannon, Rusch, Morgan, et al, 2008;Ti et al, 2012), and have identified crack use as a predictor for both HIV and HCV among street drug users (DeBeck et al, 2009;Fischer et al, 2006;Roy et al, 2001;Shannon, Rusch, Morgan, et al, 2008;Strathdee & Stockman, 2010). In Brazil, recent studies indicating comparably low (e.g., <10%) HIV and HCV prevalence levels, entailing a reduced BBV burden (Carvalho & Seibel, 2009;Cruz et al, 2013;de Azevedo et al, 2007;Nunes, Andrade, Galvão-Castro, Bastos, & Reingold, 2007). While sex work involvement is common across the Americas, crack users' residual BBV incidence in Brazil is largely attributed to sexual risk behaviors (e.g., sex work and sexfor-drug exchanges), with higher rates among females (Carvalho & Seibel, 2009;Nappo, Sanchez, & De Oliveira, 2011;Nunes et al, 2007).…”
mentioning
confidence: 99%